(3GdebGeGJ GdMQjQjIs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s ((3ESMGb Hf eMeO Hf CMeO s)
(3ChdgG (B:s
(3hHYO, aEfg LQi HHYV CfOjI GdCOH GdPj QcOJ aj gPG GdYUQ QjMg s
(3BNQgG (B:s
(3hcGfJ gPg NGJeI GdJdGbj bGd GdTjN CHheMeO GdbGSe Hf Ydj, gPG BNQ GdebGeGJ s
(3fSNI SGOSIs
(3HHYV ChQGbgG fXGe GdJYbjHIs
(3hQO CjVkG JMJ Qbe (B2186 (3COHs
(3hHMhGTjgG hHjf SWhQgG TQhM cKjQI hHgG WjGQGJ hHChdgG agQS ddebGeGJ hOaJG GdZdGa eeRbJGfs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdCOHs